Sleep medicines are often prescribed for older adults (≥75 years) without appropriate dosing instructions: A nationwide retrospective register study in Finland - Eronen, Sini-Tuulia (John Wiley and Sons Inc, 2025)
Background: Sleep medicines should be prescribed cautiously, accompanied by instructions that ensure appropriate use and reduce risks. This is especially important for older adults, for whom many of these medicines are classified as potentially inappropriate medicines.
Methods: We investigated the use and appropriateness of dosing instructions for sleep medicines (described in the Finnish National Current Care Guideline for Insomnia) prescribed for older adults (≥75 years) and dispensed with instruction label in pharmacies. The retrospective reimbursement register data for year 2020 by the Social Insurance Institution of Finland was used as the data source (1,080,843 purchases by 143,886 individuals of which 565,228 purchases were pharmacy dispenses). The appropriateness of the pharmacy dosing instructions containing keyword(s) referring to insomnia treatment was examined according to the prescribed dose, time of intake, frequency of use, and warnings/remarks. A random sample of 1000 instructions was used to manually analyze the phrasing and appropriateness.
Outcomes: We focused our analysis on 58.1% (328,285 purchases by 87,396 individuals) of the pharmacy dispenses, which contained dosing instructions referring insomnia treatment. Of these, zopiclone and mirtazapine were the most prescribed drugs (134,631 and 112,463 purchases, respectively). Dose and time of intake were specified in most of the instructions (98.4% and 83.4%, respectively), whereas frequency of use was specified in 57.3%. A small percentage of the instructions included warnings/remarks (2.8%). Overall, only 2.1% of the instructions contained information about a single dose, time of intake, temporary use, and warnings/remarks and were thus defined as sufficient. Notably, 47.7% (n = 515,615) of all the purchases in our dataset were dispensed via automated multi-dose dispensing systems, which is aimed for long-term treatment.
Interpretation: It is common to prescribe sleep medicines for older adults without appropriate dosing instructions, particularly excluding warnings against long-term, regular use. Actions to change the current prescribing practices are warranted.